Analisis Laporan Keuangan untuk Mengukur Kinerja Keuangan PT. Sri Rejeki Isman TBK (SRITEX) Periode 2020 – 2023 - Ardanisyahara Berliana Firdaus; Edi Wibowo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
PT Sri Rejeki Isman, Tbk (Sritex) is the largest textile company in Southeast Asia. The problem in this study is how the financial performance of PT Sri Rejeki Isman Tbk (Sritex) in 2020 - 2023 based on liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The purpose of this study is to provide an overview and analyse the performance conditions of PT Sri Rejeki Isman, Tbk (Sritex) in 2020 - 2023 based on liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This research is a type of case study research at PT Sri Rejeki Isman, Tbk (Sritex) for the period 2020 - 2023. The type of data used is secondary data, in the form of balance sheet reports and income statements of PT Sri Rejeki Isman, Tbk (Sritex). The results of the liquidity ratio, the average current ratio is 1.93%, indicating a bad condition. The average quick ratio is 1.03%, indicating unfavourable conditions. The average cash ratio is 0.16%, indicating a poor condition. The results of the solvency ratio, the ratio of debt to assets averaged 1.61%, indicating an unfavourable condition. The average debt to equity ratio is 2.37%, indicating poor condition. The results of the activity ratio, the average fixed asset turnover ratio is 1.30 times, indicating an unfavourable condition. The average total asset turnover ratio is 0.60 times, indicating an unfavourable condition. The results of the profitability ratio, the average return on assets ratio is -0.38%, indicating poor condition. Return on equity averaged -0.80%, indicating a poor condition. The average gross profit margin was -0.26%, indicating unfavourable conditions. The average net profit margin was -0.59%, indicating unfavourable conditions